Servant leadership relationship with leader-member exchange: The moderating role of motivation-to-serve and motivation-to-lead - Okechukwu Ethelbert Amah (International Journal of Management, Economics and Social Sciences (IJMESS), 2015)
Using 200 paired responses from managers/supervisors, and their subordinates working in three big organizations in Nigeria, this study validated the factor structure for servant leadership and combined the motivational and behavioral approaches in the servant leadership model to enhance the predictive power of servant leadership. Cross sectional survey design was used to acquire data. Principal component factor analysis and confirmatory factor analysis both confirmed that 7-factor structure was adequate for servant leadership behavior. Hierarchical regression analysis justified the combination of the motivational and behavioral approaches, since more variance in leader-member exchange was explained, compared to when only one approach was used in a model. The implications of this study are: to be effective, high motivation-to-serve is associated with low motivation-to-lead. However, in an environment of low motivation-to-serve, the secondary motive, motivation-to-lead, did not improve the prediction of leader-member exchange. Servant leadership was found to be a universal construct and not limited to any culture.
Keywords: D23; J24; 330; Servant leadership; Motivation-to-serve; Motivation-to-lead; Leader-member exchange; Cross-cultural